2016
DOI: 10.1155/2016/2908034
|View full text |Cite
|
Sign up to set email alerts
|

Differential Use of Human Neutrophil FcγReceptors for Inducing Neutrophil Extracellular Trap Formation

Abstract: Neutrophils (PMN) are the most abundant leukocytes in the blood. PMN migrate from the circulation to sites of infection, where they are responsible for antimicrobial functions. PMN use phagocytosis, degranulation, and formation of neutrophil extracellular traps (NETs) to kill microbes. NETs are fibers composed of chromatin and neutrophil-granule proteins. Several pathogens, including bacteria, fungi, and parasites, and also some pharmacological stimuli such as phorbol 12-myristate 13-acetate (PMA) are efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 60 publications
8
110
0
Order By: Relevance
“…Aleman et al observed that stimulation of these receptors with specific monoclonal antibodies induces a strong respiratory burst and an effective phagocytosis, but it does not contribute to the formation of NETs. However, it was confirmed that inducing FccRIIIB receptors with the same factors triggers the creation of NETs in a way similar to PMA stimulation [24].…”
Section: Signalling Pathways Engaged In the Net Creating Processmentioning
confidence: 91%
“…Aleman et al observed that stimulation of these receptors with specific monoclonal antibodies induces a strong respiratory burst and an effective phagocytosis, but it does not contribute to the formation of NETs. However, it was confirmed that inducing FccRIIIB receptors with the same factors triggers the creation of NETs in a way similar to PMA stimulation [24].…”
Section: Signalling Pathways Engaged In the Net Creating Processmentioning
confidence: 91%
“…To discern the effects of bosutinib on FcγRIIA alone, ROS was evaluated after FcγRIIA cross-linking of neutrophils in suspension; bosutinib reduced ROS generation with an IC 50 of 10-50 nM ( Figure 1C) while having no effect on ROS generated after PMA treatment ( Figure 1D), which directly activates the NADPH oxidase (24). FcγR engagement leads to the release of enzymes from granules (8) and neutrophil extracellular traps (NETs) (3,(25)(26)(27), a network of DNA fibers extruded by neutrophils. Bosutinib reduced FcγRIIA-mediated release of enzymes (Supplemental Figure 1C), albeit reduced cell adhesion may also contribute to these results.…”
Section: Introductionmentioning
confidence: 99%
“…It is also equally possible that the amoeba lectin binds to a neutrophil glycoprotein that in turn functions as the receptor inducing NETosis. So far, only 2 receptors on the human neutrophil have been described as bona fide inducers of NET release, the IgA receptor FcαR and the IgG receptor FcγRIIIb . In the case of human protozoan parasites as well as many other pathogens, no distinct neutrophil receptor for PAMPs has been identified .…”
Section: Discussionmentioning
confidence: 99%
“…NET formation was quantified by detecting DNA release spectrophotometrically with the DNA‐binding dye SYTOX ® Green as previously described . Briefly, neutrophils were resuspended at 1 × 10 6 cell/ml in RPMI‐1640 medium (Gibco ® ), containing 500 nM SYTOX ® Green.…”
Section: Methodsmentioning
confidence: 99%